Decision Support System on Grass Selection for Gardening Creation Using Multi-Objective Optimization on The Basis of Ratio Analysis (MOORA) - Indah Fitri Astuti; Naufal Najib; Rosmasari; Dedy Cahyadi; Rasni Alex; Awang Harsa Kridalaksana (TEPIAN, 2023)
Grass is a one-piece plant with thin, tapering leaves that grow from the base of the stem. Grass is one of the most common types of plants on earth, but not all types are the same. Some need regular care, while others can grow without ever being touched. There are various types of grass, but only a few types of grass are suitable as ornamental plants. Currently, garden construction service providers still use a manual system to determine the type of grass, so errors can occur, resulting in damage to the garden and a decrease in the artistic value and selling price of the grass. A technology can help determine the type of grass for making a garden, namely a decision support system. This system was built on a web basis using the Multi-Objective Optimization on the Basis of Ratio Analysis method to recommend types of grass for making gardens. This research uses 17 types of grass as alternative data and five selection criteria, namely leaf shape, growth rate, weather resistance, leaf color, care, leaf texture and price per meter. This method's research shows Japanese grass as the best alternative with the highest optimization value, namely -0.02499. The results of system validation using the Confusion Matrix method to compare system calculations with manual calculations obtained an accuracy value of 71%.